Mental health and psychiatry research in Brazil: scientific production from 1999 to 2003 - Razzouk, Denise [UNIFESP] (2006)
OBJECTIVE: To assess the extent of mental health scientific production in Brazil from 1999 to 2003, and to identify the nature of the publications generated, their sources of finance and the ways of publicly disseminating the research findings. METHODS: Searches for publications were conducted in the Medline and PsychInfo databases for the period 1999-2003. A semi-structured questionnaire developed by an international team was applied to 626 mental health researchers, covering each interviewee's educational background, research experience, access to funding sources, public impact and research priorities. The sample was composed by 626 mental health researchers identified from 792 publications indexed on Medline and PsychInfo databases for the period above, and from a list of reviewers of Revista Brasileira de Psiquiatria. RESULTS: In Brazil, 792 publications were produced by 525 authors between 1999 and 2003 (441 indexed in Medline and 398 in the ISI database). The main topics were: depression (29.1%), substance misuse (14.6%), psychoses (10%), childhood disorders (7%) and dementia (6.7%). Among the 626 Brazilian mental health researchers, 329 answered the questionnaire. CONCLUSIONS: There were steadily increasing numbers of Brazilian articles on mental health published in foreign journals from 1999 to 2003: the number of articles in Medline tripled and it doubled in the ISI database. The content of these articles corresponded to the priorities within mental health, but there is a need for better interlinking between researchers and mental health policymakers.